Gehirnerschütterung - Tscholl, P. M. (Sport-Orthopädie - Sport-Traumatologie, 2011)
Sports-related concussions must not be accompanied by loss of consciousness, vomit and change of behaviour, and therefore is not to be confounded with the definition of a traumatic brain injury. Athletes often report only mild symptoms, and therefore may cover them up. It is not unusual that a player may present an hour or day after the hit, and feels "just not right". Without correct treatment, symptoms may continuously be provoked, and protruded follow-up or a second impact with more often worse outcome is taken at risk. Sensitization and consciousness towards this pathophysiological process in the brain is constantly growing in sports physicians over the past years due to several publications of sport and independent medical committees. The next step is sensitization of the athletes and last but not least of their trainers and families, especially in amateur and popular sports, where primary care is organized by them. The only primary prevention is reducing such incidences by introducing more restrictive rules and recognizing fair-play as part of the game by the sport ruling body and the athletes.